Illustrating the Demands of a Performance Test Through an Interactive Multimedia Syllabus - Coniam, David (IALLT Journal of Language Learning Technologies, 2001)
This article describes the rationale for and production of a syllabus (or ’test specification’) document implemented via hyperlinked multimedia. The purpose of the multimedia program is to illustrate and exemplify the scales, descriptors and criteria for the Classroom Language Assessment (CLA) component of the English Language Benchmark Test in Hong Kong- a newly introduced language certification test for teachers of English as a Second Language (ESL). TheCLA test is a performance test of EFigure lnglish, and is assessed on the job; that is, as ESL teachers are teaching a live English lesson.